Lessons from the recent market turmoil for effective risk based supervision - Alexander, Kern (Henry Stewart Talks, 2009)
Changing structure of financial markets, Changing structure of global financial firms, Changing structure of financial markets and systematic risk, The role of regulation in Europe, Financial Services Authority risk based supervision, Principles based regulation, The credit crisis, FSA/US Capital Adequacy Regulation, UK prudential regulation: general critique, Macro-prudential regulation, Future challenges to risk based supervision/regulation